ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA - Fenti Fiqri Fadella; Riana R Dewi; Rosa Nikmatul Fajri (Universitas Bandar Lampung (UBL), 2020)
This study aims to examine and analyze how much influence Liquidity (CurrentRatio and Net Working Capital Ratio), Profitability (Return on Capital Employed, Return on Assets, Gross Profit Margin), Inflation Rate, and Company Size on Profit Growth in Pharmaceutical Companies listed on the Indonesia Stock Exchange for the period 2014-2018. There are 11 companies used as populations in this study. The sample was determined using the Puposive Sampling method and obtained a sample of 8 Pharmaceutical companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The data analysis method used is multiple linear regression model with SPSS version 20. With the results of Current ratio research, Return on Capital Employed, Return on Assets, and Inflation Rate significantly influence Profit Growth, while Net Working Capital Ratio, Gross Profit Margin, and Company size has no significant effect on profit growth.